RETRACTED: Control aspects of managing the company’s own capital - Klychova Guzaliya; Zakirova Alsou; Khusainova Amina; Klychova Aigul; Utegenova Kamshat; Nurmaganbetova Begzat (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 549, 00001 (2024), https://doi.org/10.1051/e3sconf/202454900001